Modeling and Uncertainty Quantification of Vapor Sorption and Diffusion in Heterogeneous Polymers. Issue 14 (13th August 2015) - Sun, Yunwei; Harley, Stephen J.; Glascoe, Elizabeth A.
Abstract A high‐fidelity model of kinetic and equilibrium sorption and diffusion is developed and exercised. The gas‐diffusion model is coupled with a triple‐sorption mechanism: Henry's law absorption, Langmuir adsorption, and pooling or clustering of molecules at higher partial pressures. Sorption experiments are conducted and span a range of relative humidities (0–95 %) and temperatures (30–60 °C). Kinetic and equilibrium sorption properties and effective diffusivity are determined by minimizing the absolute difference between measured and modeled uptakes. Uncertainty quantification and sensitivity analysis methods are described and exercised herein to demonstrate the capability of this modeling approach. Water uptake in silica‐filled and unfilled poly(dimethylsiloxane) networks is investigated; however, the model is versatile enough to be used with a wide range of materials and vapors.